STRATEGI PENGEMBANGAN INDUSTRI KECIL/RUMAH TANGGA (UKM) BERBASIS PERTANIAN - Purwadi, Purwadi (FORUM EKONOMI, 2015)
Small and medium enterprises (SMEs) and Industrial Appliances (IRT) in Indonesia plays an important role in absorbing labor force, increase the number of business units and support household income, so it is one important part of the economy of the country. The research objective is to develop strategies for the potential development of Small Industrial / Domestic-based Agriculture in the broad meaning in East Kutai. The study found that the right strategy for the development of Small Industrial / Domestic Agriculture based in East Kutai is to give greater attention to the process of policy formulation.Keyword: SWOT, Bumdes, Kutai Timur